Case Study: Strength of Child Witness Testimony in Cases of Sexual Abuse in Decision No. IX: 135/Pid.Sus/2023/DPK - Rosida, Lutfi Noor; Harefa, Beni Harmoni; Supardi (Sinergi International Journal of Law, 2024)
In current criminal justice practice, there have been developments regarding the use of children's testimonies, with some judges in Indonesia admitting children's statements as evidence in cases involving minors, even though we know that children are not sworn in before giving testimony. Therefore, the aim of this study is to analyze the legal strength of children's testimonies as evidence in the criminal justice system, focusing on the case with the District Court Decision Number 135/Pid.Sus/2023/PN. Dpk. This research employs a normative legal research method with a legislative approach, conducted to explore legal issues. The primary data source supporting this research includes the           District Court Decision from Depok Number: 282/Pid.Sus/2023/DPK, while secondary data consists of Law Number 35 Year 2014 concerning Amendments to Law Number 23 Year 2002 concerning Child Protection, Law Number 11 Year 2012 concerning Juvenile Justice System, and Law Number 8 Year 1981 concerning Criminal Procedure Code. The findings of this research indicate that the evidentiary strength of children's testimonies as witnesses in the Indonesian criminal justice system depends on the validity of the testimony presented in court. However, the truthfulness and probative value of such testimonies are subject to the judge's subjective assessment, and because the evaluation of witness evidence is generally non-binding, this also applies to child witnesses.